2000
DOI: 10.1021/ac000650l
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Performance Liquid Chromatography−Tandem Mass Spectrometry To Distinguish Panax ginseng C. A. Meyer (Asian Ginseng) and Panax quinquefolius L. (North American Ginseng)

Abstract: A liquid chromatography-tandem mass spectrometry (LC-MS-MS) method was developed to distinguish Asian ginseng (Panax ginseng C. A. Meyer) and North American ginseng (Panax quinquefolius L.). The method is based on the baseline chromatographic separation of ginsenoside Rf and 24(R)-pseudoginsenoside F11, two potential chemical markers present in ginseng root methanolic extracts, and their unambiguous on-line identification using tandem mass spectrometry. Consistent with the literature, 24(R)-pseudoginsenoside F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
140
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 21 publications
8
140
0
Order By: Relevance
“…A ratio of Rb 1 :Rg 1 > 3 (Ma et al, 1996;Awang et al, 2000) and ratios of Rg 1 :Re and Rb 2 :Rc < 1 have been shown to be indicative of Panax quinquefolius L. (Chan et al, 2000;Wang et al, 1999). The most powerful marker is the absence of Rf, a ginsenoside not found in AG and distinctive for Asian ginseng (Ma et al, 1996;Awang et al, 2000;Chan et al, 2000;Li et al, 2000). These criteria were met by both batches of AG.…”
Section: Resultsmentioning
confidence: 99%
“…A ratio of Rb 1 :Rg 1 > 3 (Ma et al, 1996;Awang et al, 2000) and ratios of Rg 1 :Re and Rb 2 :Rc < 1 have been shown to be indicative of Panax quinquefolius L. (Chan et al, 2000;Wang et al, 1999). The most powerful marker is the absence of Rf, a ginsenoside not found in AG and distinctive for Asian ginseng (Ma et al, 1996;Awang et al, 2000;Chan et al, 2000;Li et al, 2000). These criteria were met by both batches of AG.…”
Section: Resultsmentioning
confidence: 99%
“…Rf content in P ginseng root is more than 0.021%, whereas the contents of 24(R)-pseudoginsenoside F11 is 1/700 of Rf [18] .…”
Section: Contents Of Gs In P Quinquefoliummentioning
confidence: 92%
“…2B) dmd.aspetjournals.org though we used a standardized extract, it was still a mixture of many chemical constituents. At least 31 individual ginsenosides have been isolated from ginseng, but Rb1, Rb2, Rc, Rd, Re, and Rg1 account for Ͼ90% of the total content (Li et al, 2000). Most of the ginseng species contain other chemical entities, including polysaccharides, peptides, fatty acids, and polyphenolic compounds (Attele et al, 1999).…”
Section: Effect Of Individual Ginsenosides On Cyp1a2 Catalytic Activitymentioning
confidence: 99%